Integrated surveillance system with mobile application - Hassan Basri, A.H.; Ibrahim, Siti Noorjannah; Abdul Malik, Noreha; Asnawi, Ani Liza (IEEE, 2018)
In today’s life with the influence and vast usage of Internet of Things (IoT), a surveillance system become an essential needs (no longer a luxury facility) to home residents, buildings and other important premises. This project deals with web-based and mobile app surveillance system using Raspberry Pi and its supporting components i.e., Pi Camera, PIR motion sensor, Ultrasonic sensor, web-based & mobile application. This proposed solution can be implemented over the internet using any computer and mobile devices from anywhere and anytime. The use of Raspberry Pi has given the ability to operate and control the motion detectors, distance of the intruders and video cameras for remote sensing and surveillance. The cameras automatically stream live video and the raspberry pi device will send an alert via email and SMS to the facility owners’ computer or mobile devices. It is considered as a cost-effective solution, customizable and easy to implement by the home residents outside their home residents in comparison with other commercial surveillance system products such as CCTV, IP Camera, etc.